Meeting the Needs of Youths’ Spirituality: A Da’wah Strategy of Teras Da’wah in Yogyakarta - Ravida Chauria Shavir,; Asmaji Muchtar, (Jurnal Komunikasi Islam, 2022)
This study examines the Islamic proselytising strategy of Teras Da’wah in meeting young Muslims’ spiritual needs in Yogyakarta. Utilising a descriptive qualitative approach, the results of the study point out that Teras Da’wah as a da’wah institution wherein a captive targeted audience is younger adult Muslims, has offered the strategy of da'wah encompassing da'wah messages (themes), methods, environments, and study sessions of Islam suit to the nature of younger people. This da'wah institution, for example, is able to package the names of provisions for Islamic learning associated with young nature, such as ngaji santai and ngaji asyik. It is also possible to design study sessions in a comfortable manner, including using cyber media for communication amongst congregations. Hence, the presence of Teras Da'wah community has succeeded in encouraging young people to actively participate in religious and spiritual activities.